Akibat Hukum Yang Terjadi Pasca Kepailitan Pada Perseroan Terbatas - Happy Yulia Anggraeni (Jurnal Media Justitia Nusantara, 2017)
Companies engaged in business are legal entities and some are not incorporated. One company that is a legal entity is a Limited Liability Company (PT). Specifically, a Limited Liability Company is regulated in Law No. 40 of 2007 concerning Limited Liability Companies (UUPT) which are effective from August 16, 2007. In Law No. 40 of 2007 concerning Limited Liability Companies, also regulated several provisions concerning bankruptcy that occur because of errors or negligence of the board of directors and bankrupt assets is not enough to pay all the obligations of the company in bankruptcy, each member of the board of directors jointly and severally responsible for all obligations that are not repaid from property bankruptcy. The problems in the paper are: How is a Limited Liability Company stated in bankruptcy conditions and what impact can it cause when a Limited Liability Company is declared bankrupt. The approach method used in this study uses a normative juridical approach. The research specification used is descriptive analytical, namely research that aims to provide a description of the research subject. Data for this research are sourced from secondary data supported by primary data. This study will examine secondary data. Data analysis was carried out on data with a qualitative approach, namely the data that had been collected was sorted and processed. After being sorted and processed then analyzed logically and systematically. The results of the discussion indicate that a bankruptcy of a PT is bankruptcy of itself not bankruptcy of the management, even though the bankruptcy occurs because of negligence of the management so that the board should not be held accountable jointly for the loss due to negligence and can only be held accountable if wealth the company is not enough to cover losses due to bankruptcy. The impact caused when a Limited Liability Company is declared to be in a bankrupt condition is that the debtor for the law loses the right to control and manage the assets that are included in the bankrupt assets as of the decision of the  ankruptcy statement. The PT Legal Entity, not automatically disbanded and the dissolution of the PT Legal Entity still uses the GMS procedure as the highest organ in PT. The implementation of the Dissolution of the PT Legal Entity was carried out after the management and settlement of the company was  ompleted. The dissolution of PT after the bankruptcy verdict was read can only be requested by the creditors of the court with the reason that the company was unable to pay its debt after it was declared bankrupt or the company's assets were not enough to pay off all of its debts after the bankruptcy statement wasrevoked.